Survey Evaluasi Pembelajaran Perkembangan Peserta Didik oleh Mahasiswa Baru Program Studi PGSD - Artini, Ni Putu Juni; Isyarotullatifah, Isyarotullatifah; Febryan, Irwan; Astuti, Ni Made Ignityas Prima (Indonesian Research Journal on Education, 2022)
Student development is one of the basic subjects for student especially elementary school (PGSD)study program at Triatma Mulya University. This research is a descriptive research that aims todetermine the results of the evaluation of all new students of elementary school (PGSD) studyprogram at Triatma Mulya University on student development learning. The location of thisresearch was conducted at Triatma Mulya University PSDKU Jembrana with research subjects all new students of elementary school (PGSD) study program that is 18 people. Data collectioninstruments using questionnaires consisting of 14 (fourteen) statements on a 1-4 linkert scale. Thisquestionnaire was tested for validity and reliability using SPSS. The data processing techniqueused in this study is descriptive statistics by accumulating the number of points from eachstatement item that is visualized into a graph. Based on the research, the results of the evaluation of student development learning by new students of elementary school (PGSD) study program at Triatma Mulya University in 2021 are very good, it can be seen from the accumulation of the number of percentages who agree and strongly agree more than those who disagree. There are no students who strongly disagree with the statement items given.